Psychological characteristics and mental health problems in mexican students: A structural analysis - Juárez-García, Arturo (2016)
The objective of this study was to propose a structural model that delineates the relationship between different psychological characteristics in relation to mental health problems through a structural equation model. In a non-random, intentional sample of N = 231 students, the specified model demonstrates that anger-trait, self-denial and internal locus of control variables have effects on mental health problems through mediators such as anger-in, lack of assertiveness, and self-efficacy, and that they keep the expected theoretical relationships (X2 = 50.24, gl = 35 and p = 0.04; razón X2/gl = 1.44, CFI = .98, NFI = .93, IFI = .98, RMSEA = .04) These findings are discussed in terms of their contribution to understanding the mechanisms of the complex relationship among psychological characteristics, personality and health.